2009
DOI: 10.1007/s10165-009-0179-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-dose mizoribine pulse therapy in combination with methotrexate in rheumatoid arthritis patients with an insufficient response to methotrexate

Abstract: The aim was to determine the efficacy of low-dose intermittent pulse administration of mizoribine (MZR), a purine synthesis inhibitor, in combination with methotrexate (MTX) to control the symptoms of rheumatoid arthritis (RA) in patients with an insufficient clinical response to MTX alone. Twenty-seven patients with active RA, despite treatment with MTX, were enrolled and given MZR in combination with MTX and continued for 24 weeks. The primary endpoint was assessment of clinical improvements using the Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…The clinical efficacy of MZR was first approved in renal transplant recipients (4,5). Since then MZR has been thought to be safe and well tolerated compared with other immunosuppressants, and recent studies havelogical RA treatments in Japan (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical efficacy of MZR was first approved in renal transplant recipients (4,5). Since then MZR has been thought to be safe and well tolerated compared with other immunosuppressants, and recent studies havelogical RA treatments in Japan (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that oral MZR pulse therapy, which is associated with increased serum levels of MZR, may be associated with greater clinical efficacy without significant increase in clinical toxicity when [18][19][20][21]. Additionally, Tsubouchi et al [22] describe a patient with lupus nephritis (WHO class V) who was successfully treated with MZR.…”
Section: Discussionmentioning
confidence: 95%
“…One 3-month and one 12-month trial indicated that the single-dose regimen seemed to increase the efficacy of MZR safely [11,12]. Additional pulse administration of MZR with MTX was reported to have some degree of effectiveness for the control of inflammation in patients showing escape or resistance to MTX monotherapy [13][14][15][16]. On the other hand, no clinical studies have focused on the effect of a change in the dosing regimen, and the present study was therefore performed to address this issue.…”
Section: Discussionmentioning
confidence: 99%